CIRCUMVENTION DALAM PERDAGANGAN INTERNASIONAL: IMPLIKASI TUDUHAN VIETNAM TERHADAP INDONESIA - SRI MULYANA LIHAWA; WAODE MUSTIKA; NUR MOHAMAD KASIM; MUHAMAD KHAIRUN KURNIAWAN KADIR (GANEC SWARA, 2024)
Cross-border trade is something that can no longer be avoided in today's era of globalization. Countries conduct business activities in order to advance their economic activities. In these activities, many countries do things that harm business principles. One of them is the evasion action. This research aims to determine the regulation of circumvention measures in international trade. This article uses normative legal research methods based on the international economic legal framework. The research results show that circumvention measures constitute a form of evasion of anti-dumping import duties. These actions involve manipulation or changes in the way trade is conducted to avoid paying high import duties. In Indonesia, anti-dumping regulations do not specifically regulate circumvention issues.